Studies on the Rhagophthalmidae (Coleoptera) from China, part II. Three new species of Diplocladon Gorham, 1883 - Wang, Cheng-Bin; Kundrata, Robin (Zootaxa, 2024)
Three new rhagophthalmids of the genus Diplocladon Gorham, 1883 are described from China, i.e. D. maai sp. nov. from Fujian, D. nezha sp. nov. from Yunnan, and D. wukong sp. nov. from Chongqing. Diplocladon atripenne Yiu, 2017 is redescribed and first recorded from Guangdong and Guangxi. Illustrations of the habituses and diagnostic characters of all four Chinese species are provided; a key to Chinese species of Diplocladon based on males is compiled; and a map is presented to exhibit their distributions.